Augmented Reality with Mobility Awareness in Mobile Edge Computing over 6G Network: A Survey - Loutfi, Soule Issa; Tureli, Ufuk; Shayea, Ibraheem (IEEE, 2023)
Augmented reality (AR) technology is an advancement that allows users to see the real world through the use of a virtual device. The explosive manufacturing of mobile devices follows a rise in the popularity of mobile phones and allows the user to run AR applications based on the mobile with substantial mobility awareness. The new generation networking technology (e.g., 6G) serves as a challenge for upcoming AR applications to attain low latency and computationally enhanced during the time that mobile edge computing (MEC) allows the user to communicate easily with AR applications. However, previous work on mobile edge computing support AR may not perform as expected in many practical cases, such as irreparable network interruptions due to wireless connectivity instability and user mobility, which is defining feature of popular AR applications. To attain low latency, deploying computational and mobility, the MEC will perform a major role in either fifth generation (5G) or six-generation (6G) networking. This paper studies in general the AR concept and the utility of mobility management in MEC applications that can be implemented in the next generation of mobile by reviewing the user to connect their interface. This paper discusses augmented reality and mobility challenges. The future direction and solution for the implementation of AR based mobility aware and MEC are also analyzed. This survey will contribute a comprehensive of the issues associated with mobility management, specifically concerning augmented reality with mobility awareness in future.